Re-imagining scientific communities in post-apartheid South Africa : a dialectical narrative of black women’s relational selves and intersectional bodies - Liccardo, Sabrina (My University, 2016)
The focus of this research study is on black South African women’s experiences of being science students, becoming graduates and professionals, and the ways in which they navigate institutional and disciplinary spaces that have historically been dominated by white masculinities. Women scientists are living in a critical era as the socio-cultural and political-economic landscape is transforming rapidly, affecting changes in aspects of identity and processes of identification. The individual life histories of black South African women scientists provide a telling story of a society in transformation because they experience the world as an outlier group; paradoxically positioned within an interstitial space between their dual sense of belonging to and alienation from a marginal and an elite group. The racialised gender gap in STEM (Science, Technology, Engineering and Mathematics) disciplines raises critical concerns around the political nature of scientific enquiry and whether black women will achieve equity in society and economic empowerment if they continue to be marginalised from society’s power structures. Little is known about their journeys into becoming the new generation of scientists in post-apartheid South Africa. Using a narrative method to enquire into the lives of 14 young women, the aim of the study was to critically examine questions of discursive, material and symbolic elements that emerge within their narratives across temporal shifts, and how these new meanings reflect specific subjectivities, reconfigure their dynamic social identities and transform time into ‘other spaces’ of belonging beyond categories of social divisions.